Salivary bypass tube in total laryngectomy: Systematic review and meta‐analysis. Issue 11 (3rd August 2022) - Costantino, Andrea; Pace, Gian Marco; Festa, Bianca Maria; Ferreli, Fabio; Malvezzi, Luca; Spriano, Giuseppe; Mercante, Giuseppe; De Virgilio, Armando
Abstract: The aim of this study is to determine whether the preventive positioning of a salivary bypass tube (SBT) after total laryngectomy (TL) reduces the incidence of postoperative pharyngocutaneous fistula (PCF) and pharyngeal stenosis (PS). This study was conducted in conformity with the PRISMA statement. 1960 patients with a median age of 62.0 years were included. A SBT was placed in 980 (50%) patients (SBT group). The cumulative PCF incidence in the SBT group was 15.8% (95% CI: 9.3–23.6). The measured pooled OR comparing PCF incidence in patients with SBT compared to those without was 0.40 (95% CI: 0.24–0.65). The pooled PS incidence in the SBT group was 12.3% (95% CI: 5.4–21.6). The measured pooled OR comparing PS incidence in patients with SBT compared to those without was 0.43 (95% CI: 0.24–0.65). PCF and PS could be prevented by the intra‐operative placement of a SBT.